Routine healthcare for families in transition after a natural disaster - Gisele Cristina Manfrini Fernandes; Astrid Eggert Boehs (Universidade de São Paulo, 2013)
OBJECTIVE: to present the healthcare routines of families in transition after natural disasters based on the Family Routines and Rituals theoretical framework. METHOD: this qualitative study of multiple cases was developed based on six rural families in southern Brazil, 2 years after a natural disaster. The data were collected through participant observation, interviews, narratives, genograms, ecomaps, and routine calendars, and a narrative analysis was conducted. RESULTS: families showed notable episodes of illness that required professional assistance during post-disaster care, daily routine care, and other routines associated with healthcare services. CONCLUSION: these results reinforce the need for nurses to attend to family experiences during transitions after natural disasters and to prepare for the changes and needs with regard to healthcare and its promotion.